Letter (copy) : Donation - Tewson, Vincent
030-0184-001 Secretary's. HVT/EK/1014. 9th May, 1938. Miss Mary Sutherland, Spanish Relief Committee, Transport House, Smith Square, London, S.W.1. Dear Miss Sutherland, DONATION Referring to your letter of the 25th April and our subsequent telephone conversation, I am enclosing a cheque for £30 as a grant from the International Solidarity Fund to enable your Knitting Committees to continue their work. Yours sincerely, Assistant Secretary. Cheque £30. 292/946/30/184